Effect of Stirring Technique Variations and Roasting Time on the Chemical, Microbiological, and Sensory Characteristics of Shredded Spiced Fish - Puan Mutia Ayunisa; Dewi Sartika; Gusri Akhyar; Sri Hidayati; Sussi Astuti (The University of Lampung, 2026)
Lampung Province is known as one of the producers of freshwater fish in Indonesia, with Ranau tilapia as its superior commodity. This fish is known for its thick, dense flesh and free from muddy odor, making it very suitable for use as a raw material for processed value-added products such as shredded spiced fish. However, traditional production methods still have limitations in terms of efficiency and risk of contamination. This study aims to determine the interaction and optimal results between mechanical and conventional stirring methods combined with five variations of roasting time (60, 75, 90, 105, and 120 min). Fresh Ranau tilapia was mixed with selected spices and processed based on these variations. The results showed that the interaction between stirring technique and roasting time significantly influenced the chemical, microbiological, and sensory characteristics of the final product. Optimal treatment, stirring using a machine for 105 min (M2S4), produces shredded spiced fish that meets the Indonesian National Standard (SNI), with a moisture content of 9.80%, ash content of 4.06%, protein content of 38.57%, and microbiological safety of 1.53 log CFU/g. Sensory evaluation also shows a high level of consumer acceptance. This technological innovation increases production efficiency, ensures consistent product quality, and becomes a reference model for MSMEs in developing a competitive and sustainable local food industry.